Seasonal patterns in B‐vitamins and cobalamin co‐limitation in the Northwest Atlantic - Catherine Bannon; Patrick L. White; Elden Rowland; Kiran J. More; Anna Gleason; Megan Roberts; Emmanuel Devred; Lindsay Beazley; Julie LaRoche; Erin M. Bertrand (Limnology and Oceanography, 2025)
B‐vitamins are important co‐enzymes that have long been hypothesized to play key roles in marine ecosystems. However, environmental measurements remain scarce, which limits our understanding of their potential impact. Here, we present mass spectrometry‐based measurements of B‐vitamins (B 1 , B 2 , B 3 , B 5 , B 6 , B 12 ) and related vitamers along a transect in the Northwest Atlantic Ocean, in both particulate phase and dissolved in seawater, seasonally over 5 yr. We then couple these data with targeted investigations of the impact of B 12 (cobalamin) on phytoplankton growth. We show that these metabolites are present at femto‐ to pico‐molar concentrations and demonstrate that season explains most variance in particulate phase B‐vitamins but not dissolved, offering further evidence that metabolite inventories in these two phases are often decoupled. We find positive correlations between particulate organic carbon with particulate B 1 and B 3 , and between chlorophyll a and particulate B 2 and 5,6‐dimethylbenzimidazole in fall but not spring, indicating unique seasonal drivers of vitamin inventories. Of all measured vitamins, only cobalamin was enriched in the particulate over dissolved phase, predominantly in spring. We documented nitrogen and cobalamin co‐limitation of phytoplankton growth during spring bloom decline, when dissolved cobalamin is seemingly drawn down, but not during fall, when dissolved cobalamin concentrations remain elevated. These seasonal differences may be underpinned by the increased importance of cobalamin remodeling and recycling during the fall. This study provides insights into the absolute concentrations, stoichiometry, and variability of B‐vitamins in the ocean and offers evidence that cobalamin exerts seasonally varying controls on Northwest Atlantic marine ecosystems.

Production and utilization of pseudocobalamin in marine Synechococcus cultures and communities - Catherine C. Bannon; Maria A. Soto; Elden Rowland; Nan Chen; Anna Gleason; Emmanuel Devred; Julie LaRoche; Erin M. Bertrand (Environmental Microbiology, 2024)
Cobalamin influences marine microbial communities because an exogenous source is required by most eukaryotic phytoplankton, and demand can exceed supply. Pseudocobalamin is a cobalamin analogue produced and used by most cyanobacteria but is not directly available to eukaryotic phytoplankton. Some microbes can remodel pseudocobalamin into cobalamin, but a scarcity of pseudocobalamin measurements impedes our ability to evaluate its importance for marine cobalamin production. Here, we perform simultaneous measurements of pseudocobalamin and methionine synthase (MetH), the key protein that uses it as a co‐factor, in Synechococcus cultures and communities. In Synechococcus sp. WH8102, pseudocobalamin quota decreases in low temperature (17°C) and low nitrogen to phosphorus ratio, while MetH did not. Pseudocobalamin and MetH quotas were influenced by culture methods and growth phase. Despite the variability present in cultures, we found a comparably consistent quota of 300 ± 100 pseudocobalamin molecules per cyanobacterial cell in the Northwest Atlantic Ocean, suggesting that cyanobacterial cell counts may be sufficient to estimate pseudocobalamin inventories in this region. This work offers insights into cellular pseudocobalamin metabolism, environmental and physiological conditions that may influence it, and provides environmental measurements to further our understanding of when and how pseudocobalamin can influence marine microbial communities.

Remotely sensed habitat diversity predicts species diversity on coral reefs - Anna C. Bakker; Arthur C.R. Gleason; Alexandra C. Dempsey; Helen E. Fox; Rebecca H. Green; Sam J. Purkis (Remote Sensing of Environment, 2024)

Heat, human, hydrodynamic, and habitat drivers measured from space correlate with metrics of reef health across the South Pacific - Anna C. Bakker; A. C. R. Gleason; A. Mantero; A. C. Dempsey; S. Andréfouët; A. R. Harborne; S. J. Purkis (Coral Reefs, 2023)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.